Bifunctional Platinated Nanoparticles for Photoinduced Tumor Ablation. Issue 46 (7th October 2016) - Guo, Zhengqing; Zou, Yelin; He, Hui; Rao, Jiaming; Ji, Shuangshuang; Cui, Xiaoneng; Ke, Hengte; Deng, Yibin; Yang, Hong; Chen, Chunying; Zhao, Yuliang; Chen, Huabing
Abstract : Bifunctional self‐assembled nanoparticles with a platinated fluorophore core with ultralow radiative transition are developed, which can generate both singlet oxygen and the photothermal effect for synergistic photodynamic and photothermal therapy with tumor ablation.